PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN ROLE MODEL TERHADAP INTENSI BERWIRAUSAHA BAGI MAHASISWA STTI BONTANG - Irianto; Santoso (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
In Indonesia, entrepreneurship is one of the important factors that can encourage the economic growth of a nation. Thus, it is important to encourage interest and entrepreneurial abilities among Indonesian people, including STTI Bontang students. This research aims to analyze the influence of entrepreneurship education and role models on entrepreneurial intentions for STTI Bontang students. This research uses qualitative research methods using literature in the form of libraries, such as books, notes, theses, journals and several relevant research results. Apart from using literature studies, the author also made personal observations. This research method involves in-depth interviews. The research results show that entrepreneurship education and role models have a positive effect on entrepreneurial intentions for STTI Bontang students. Entrepreneurship education can increase knowledge, skills and entrepreneurial attitudes. The interaction between entrepreneurship education and role models shows a strong synergy, where students who benefit from these two factors show higher entrepreneurial intentions. There are supporting and inhibiting factors. Therefore, efforts need to be made to increase entrepreneurship education and role models for students. This is done to increase the role of role models and increase cooperation with stakeholders.